Developing Academic Supervision Model Assisted by The Information System Management on Geography Teachers of Senior High School in Pekalongan Regency - Sugiyono, Sugiyono; Hardyanto, Wahyu; Masrukan, Masrukan (Educational Management, 2019)
The development of academic supervision model assisted by the Information System Management is an academic supervision model by using a web tool. The purpose of this study is to describe the implementation of current supervision, develop a model, validate the model and analyze the practicality of the model. The method of this research is Research and Development. In the preliminary study, literary studies, field studies and descriptions of findings’ analysis were carried out. Data collection techniques were done by using interviews, questionnaires and observations. The development stage included the conceptual development, model validation involving experts and practitioners. The evaluation staged used an assessment sheet to find out the practicality of the model. Based on the results of the preliminary research, an academic supervision model assisted by the Information System Management was developed. Then the conceptual model was validated by experts and practitioners to produce valid models and then limited trial were conducted. The conclusions in this study are: (1) factual models of academic supervision still have weaknesses; (2) the model developed was validated with a very good level of validity; (3) the model developed was practical and effective to be used by supervisors to carry out the academic supervision. Suggestions from this study were expected not only to be tested on a limited scale but also can be continued a broader scale.